Evaluation of Diuron (3-[3,4-dichlorophenyl]-1,1-dimethyl urea) in a Two-stage Mouse Skin Carcinogenesis Assay - Ferrucio, Bianca [UNESP] (2010)
Diuron (3-[3,4-dichlorophenyl]-1,1-dimethyl urea) is an herbicide with carcinogenic activity in rats and mice, which have developed respectively urothelial and mammary gland tumors in long-term studies. Accordingly, diuron has been categorized as a "likely human carcinogen" by the U. S. Environmental Protection Agency. Although the carcinogenesis-initiating activity of diuron has been reported in an early initiation-promotion mouse skin study, its genotoxic potential has been disputed. It is necessary to clarify the mode of action through which it has caused rodent neoplasia and verify its relevance to humans. Herein, two experiments were developed to verify the initiating and promoting potentials of diuron in a twenty-three-and a twenty-one-week-long mouse skin carcinogenesis protocol. In one, dimethylsulfoxide (DMSO) was the solvent for the herbicide; in the other, acetone was the alternative solvent in order to verify whether DMSO had inhibitory influence on a potential cutaneous carcinogenic activity. The adopted schedule for the tumor-promoting agent 12-O-tetradecanoylphorbol 13-acetate (TPA) resulted in skin ulcers, which demonstrates the need for careful selection of TPA dose levels and frequency of application in this model. In both studies, diuron did not exert any influence on the skin carcinogenesis process, in contrast with results already reported in the literature.